Трансформація концептуальних положень системи підготовки вчителів іноземних мов у США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (Видавництво СумДПУ імені А. С. Макаренка, 2020)
Резюме. Метою статті є аналіз трансформацій концептуальних положень у галузі підготовки вчителів іноземних мов у США. Дослідження виконано із застосуванням методів системного аналізу й узагальнення тенденцій розвитку теоретико-методологічних засад сфери іншомовної педагогічної освіти. З’ясовано, що в сучасній науково-світоглядній картині американських освітян на передній план виступили концептуальні ідеї соціалконструктивізму, критичної педагогіки, гуманізму й постпозитивістька епістемологія, оформившись у соціокультурній парадигмі. Основними тенденціями розвитку методологічних підвалин галузі є перехід від трансмісійної до колаборативної, транзакційної та перетворювальної моделей у вищій освіті; від тренувальної до розвивальної парадигми підготовки вчителів-філологів; відбувається переосмислення ролі студента в процесі навчально-професійної діяльності. Оновлена концептуальна парадигма характеризується відмовою від ідеї прямолінійності в розбудові наукового знання на користь переосмислення ролі особистості в перетворенні знаннєвої бази, освітнього середовища та соціокультурного контексту.

Abstract. The present paper examines transformations of conceptual orientations in the field of foreign language teacher education in the USA. In the study the methods of systematic and retrospective analysis were employed to outline the tendencies in the development of theoretical background of the sphere of language teacher preparation. The foundational theories informing the contemporary academic outlook of American educators are the constructivism, social constructivism, critical pedagogy, humanism, postpositivist epistemology and sociocultural perspective. One of the main developmental trends in the sphere of language teacher education is characterized by the shift in the instructional models from transmission to collaboration, transaction and transformation. The training approach in teacher preparation is rethought in the perspective of teacher education as development. A discernible shift has taken place in the perception of the role of student-teachers as active transformers of information, who not only consume the relevant theories but also act as co-authors of the professional knowledge base; from being the objects of educational influence and instructional process to its subjects. One of the general research trends is the focus on the problem of learning to teach as opposed to the previously emphasized teaching students to teach. Recent research also suggests criticism of technicist view in teacher preparation (developing a predefined set of basic knowledge and teaching skills) towards actively engaging future foreign language teachers in the critical evaluation of multiple theoretical perspectives. In the sphere of language teacher training the prescriptive, dogmatic pursuit of universal educational theory, as well as an ideal foreign language teaching approach are reconsidered in light of pluralism, changeability, epistemic and gnoseological variability. Thus, the contemporary conceptual paradigm of the sphere of language teacher education is characterized by rejection of the idea of straightforwardness in the construction of educational theory in favor of individual, context and culture specific interpretation.

Резюме. Целью статьи является анализ трансформаций концептуальных положений области подготовки учителей иностранных языков в США. Исследование выполнено с применением методов системного анализа и обобщения тенденций развития теоретико-методологических основ сферы иноязычного педагогического образования. Установлено, что в США на передний план педагогического образования выступили концептуальные идеи социалконструктивизма, критической педагогики, гуманизма и эпистемология постпозитивизма, которые оформились в социокультурной парадигме. Основными тенденциями развития методологических основ отрасли является переход от трансмиссионной к колаборативной, транзакционной и преобразовательной моделей высшего образования; от тренировочной к развиваящей парадигме подготовки учителей-филологов; происходит переосмысление роли студента в процессе учебнопрофессиональной деятельности. Современная концептуальная парадигма характеризуется отказом от идеи прямолинейности в развитии научного знания в пользу переосмысления роли личности в развитии теории, образовательной среды и социокультурного контекста.
Transformations in the conceptual orientation of the US system of foreign language teacher education
Трансформация концептуальных положений системы подготовки учителей иностранных языков в США
https://repository.sspu.edu.ua/handle/123456789/9041
Keywords: система підготовки вчителів іноземних мов; концептуальні положення; трансформація; наукове знання; США